Fabrication And Dosimetric Characterization Of Novel Tissue-Equivalent Rhizophora Spp. Phantoms For Radiation Therapy Applications - Oluwafemi, Samson Damilola (2021)
Phantoms constructed from tissue-equivalent materials (TEMs) are used to assess radiation dose delivered to patients and evaluate the quality of radiological imaging systems. However, very few of these materials have been developed for dose estimations with low and high energy photon and high energy electron beams using Rhizophora spp. (R. spp.) particleboards with a bio-based adhesive. The design, fabrication and properties of R. spp. particleboards as novel tissue-equivalent phantom material (TEPM) with suitable dosimetric properties at diagnostic and therapeutic photon and therapeutic electron energies are described.